1987
DOI: 10.1111/j.1365-2621.1987.tb05923.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Taurocholate by Pectin in the Presence of Calcium Ions

Abstract: Binding of taurocholate by pectin was examined in vitro, using lowmethoxyl pectin and calcium lactate. Water in calcium pectate gel was partially separated from the gel by filtration through a glass-filter. Taurocholate bound by pectin was calculated after measurement of taurocholate in the filtrate by the UV absorption method. The amount of taurocholate bound by pectin increased linearly with increase in pectin concentration but independent of time. One gram pectin bound a maximum of 6.0 Pmole of taurocholate. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
1
1
Order By: Relevance
“…In this instance, it is possible that Ca 2+ forms bridges between the acid groups of BA and the free COOH of pectin. In some studies such bridges of di-or trivalent cations are discussed [11,15,17]. There was no evidence from the present experiments for an enhancement of the interaction between BA and pectin in the presence of Ca 2+ .…”
Section: Resultscontrasting
confidence: 67%
“…In this instance, it is possible that Ca 2+ forms bridges between the acid groups of BA and the free COOH of pectin. In some studies such bridges of di-or trivalent cations are discussed [11,15,17]. There was no evidence from the present experiments for an enhancement of the interaction between BA and pectin in the presence of Ca 2+ .…”
Section: Resultscontrasting
confidence: 67%
“…45) Bile acid adsorption by dietary fiber in vitro has also been reported for many fiber types. 46) In addition polyphenols such as flavonoids and tannins have been shown to have numerous health protective benefits of which include lowering of blood lipids. Furthermore recent reports have suggested that several plant sterols reduce serum cholesterol by the inhibition of intestinal cholesterol absorption.…”
Section: Discussionmentioning
confidence: 99%